علاقة بعض المؤشرات العضلية والنوم باستخدام معيار هوبر Hooper للتقييم الذاتي بإنجاز 1500م - الكناني، محفوظ فالح حسن (جامعة القادسية - كلية التربية الرياضية, 2015)
الأهداف: التعرف على علاقات الارتباط بين مستوى التعب والاجهاد والالم العضلي والنوم مع إنجاز ١٥٠٠ متر العينة: عدائي المسافات المتوسطة (١٥٠٠ متر) فئة الناشئين والبالغ عددهم (٦) ستة عدائين اختير (٣) ثلاثة من نادي الميناء الرياضي حيث بلغت نسبتهم من مجتمع الأصل (١٠٠%) و(٣) ثلاثة من نادي البصرة الرياضي حيث بلغت نسبتهم (١٠٠%) من مجتمع الأصل. الاختبارات والقياسات ١-تم تقييم مؤشرات التعب والالم العضلي والاجهاد والنوم وفق معيار هوبر Hooper من خلال استمارة معتمدة لهذا الغرض ٢-تم قياس النبض والضغط الدموي الانقباضي وزمن استعادة الاستشفاء بعد إنجاز ١٥٠٠م مباشرة. نتائج البحث: ١-ظهور علاقة متبادلة ومؤثرة بين حالة النوم عند العدائين وإنجاز ١٥٠٠م. ٢-تأثر النبض بعد الإنجاز وبشكل معنوي في تقييم الالم العضلي والاجهاد والنوم عند العدائيين. التوصيات: اعتماد التقييم الذاتي وبشكل دوري لكشف ما يعانيه الرياضي لمؤشرات التعب والالم العضلي والإجهاد.
Objectives: To identify the correlations between the level of fatigue, stress and muscle pain and sleep with the completion of 1500 meters. Sample: middle-distance runners (1,500 meters), the junior class's (6) six runners selected three (3) of the athletic port club with a percentage of the original community (100%) and three (3) of Sports Basra Club reaching percentage (100%) of the original. Tests and measurements: 1- was assessed indicators of fatigue and muscular pain, stress and sleep according to standard Hooper Hooper through the form approved for this purpose. 2- was measured pulse and blood pressure and systolic time of hospitalization after the completion of the restoration of 1500 m directly. Search results: 1- The emergence of a reciprocal relationship between the state and moving runners and sleep at the completion of 1500. 2- influenced by the pulse after a significant achievement and in the evaluation of muscular pain, stress and sleep at hostile. Recommendation: The adoption of self-assessment on a regular basis to detect the suffering of Sports indicators of fatigue and muscular pain, stress and sleep according to standard Hooper adopted what these indicators of a direct impact on the completion of 1500 m.
Keywords: الألعاب الرياضية -- رياضة الجري -- التقييم الذاتي -- معيار هوبر